Obstetric and neonatal factors associated with preterm birth: a five-year cohort - Vaz, Simone Minuzzi Catto; Kleibert, Karine Raquel Uhdich; Rebelato, Cibele Thome Da Cruz; Schultz, Carmen Cristiane; Colet, Christiane de Fátima (O Mundo da Saúde, 2023)
Premature birth constitutes a moment of vulnerability for the newborn, requiring greater care and attention. Therefore, the objective of the study was to analyze obstetric and neonatal factors, related to the outcome, of newborns admitted to a Neonatal Intensive Care Unit born at term and prematurely. This is a cohort, documentary and retrospective study. Clinical, epidemiological and care variables were collected directly from the medical records and discharge summaries of newborns, hospitalized from January 2016 to December 2020, analyzed with descriptive and inferential statistics. 494 newborn hospitalizations were analyzed. Around 70% of these were premature newborns. A relationship was found between premature birth and obstetric characteristics: low number of prenatal consultations (p<0.001), vaginal birth (p= 0.04), complications (p<0.001) and use of antibiotics during pregnancy (p=0 .02), occurrence of ruptured membranes (p<0.001) and antenatal corticosteroid therapy (p<0.001). And, statistically significant difference between prematurity and: sex (p=0.01), twin birth (p<0.001). And, between prematurity and the need for assistance interventions: use of surfactante (p<0.001), central venous access (p<0.001), ventilatory support (p=0.01), phototherapy (p<0.001), blood transfusion (p<0.001) and parenteral nutrition (p<0.001). The various factors associated with premature birth were observed, which must be monitored in order to prevent negative outcomes.